2007
DOI: 10.3171/spi-07/09/486
|View full text |Cite
|
Sign up to set email alerts
|

Use of osteogenic protein-1 in patients at high risk for spinal pseudarthrosis: a prospective cohort study assessing safety, health-related quality of life, and radiographic fusion

Abstract: Object The capability of osteogenic protein (OP)–1 to induce bone formation has led to an increasing interest in its use in fusion surgery. This prospective study examines the safety and efficacy of OP-1 use in patients considered to be at a high risk for developing pseudarthrosis following reconstructive spinal surgery. Methods Outcome measures included documentation of adverse events, radiographic eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…The rhBMP-7 has been documented as a potential treatment alternative for different diseases, including bone disease, stroke, inflammatory bowel disease, prostate cancer, and chronic renal disease 9 . More explicitly, rhBMP-7 plays an important role in bone formation by inducing differentiation of pluripotent mesenchymal cells into active osteoblasts, Furlan et al 9 concludes that it can induce a stable, mature, posterolateral spinal fusion mass more rapidly than an autologous bone graft, and the resulting fusion mass may be biomechanically stiffer in the early stages (up to 3 months) of healing.…”
Section: Discussionmentioning
confidence: 99%
“…The rhBMP-7 has been documented as a potential treatment alternative for different diseases, including bone disease, stroke, inflammatory bowel disease, prostate cancer, and chronic renal disease 9 . More explicitly, rhBMP-7 plays an important role in bone formation by inducing differentiation of pluripotent mesenchymal cells into active osteoblasts, Furlan et al 9 concludes that it can induce a stable, mature, posterolateral spinal fusion mass more rapidly than an autologous bone graft, and the resulting fusion mass may be biomechanically stiffer in the early stages (up to 3 months) of healing.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Jeppsson et al observed bony bridging at the fusion site in only one of four rheumatoid patients treated with wire fixation and rhOP-1 for atlantoaxial instability (34). On the other hand, Fehlings and coworkers have demonstrated fusion rates exceeding 80% using rhOP-1 in patients at high risk for pseudoarthrosis undergoing cervical or lumbar fusion (17,35). The initial randomized controlled trials of rhOP-1 compared use of rhOP-1 to autograft in a small number of patients (<40) undergoing posterolateral lumbar fusion (36)(37)(38)(39).…”
mentioning
confidence: 96%
“…Both rhBMP-2 and rhOP-1 demonstrated efficacy in inducing bone formation in preclinical animal studies, which has spurred clinical investigation of their efficacy as bone graft substitute (13)(14)(15)(16). Moreover, other investigators have suggested that BMPs, including OP-1, may show promise in promoting fusion in patients with high-risk adverse medical conditions (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested that some modification of either the surgical technique or the carrier may be required for extensive use of OP-1 in instrumented posterolateral lumbar fusion. Furlan et al 168 reported good fusion rates (80%) and improved health related quality of life (HRQOL) outcomes in a level III study using OP-1 and autograft in 30 patients with high risk of spinal pseudarthrosis. The data consisted of cases of lumbar or lumbosacral fusions as well as cervical and occipitocervical fusions for high risk cases such as previous failed fusions, rheumatoid arthritis, systemic lupus erythematosus, MaroteauxLamy syndrome, ankylosing spondylitis, steroid use, immunosuppression, heavy smokers and osteopenic or osteoporosis.…”
Section: Osteogenic Protein 1 (Op-1) In Lumbar Spinementioning
confidence: 99%